PENINGKATAN KUALITAS PELAYANAN PUBLIK DALAM RANGKA REFORMASI BIROKRASI DI KANTOR PERTANAHAN KOTA SEMARANG - Riris Retno Wulan; Mochammad Mustam (Journal of Public Policy and Management Review, 2017)
Public service is one indicator of bureaucratic reform in realizing good governance. Public service quality improvement program aims to provide quality services in accordance with the expectations of the community. This study discusses the implementation of improving the quality of public services in the framework of bureaucratic reform in the Land Office of Semarang City and the factors - obstacles in the implementation of improving the quality of public services in the Land Office of Semarang City. The theory used in this research is the theory of bureaucratic reform, public service management theory and theory of community participation. Techniques of collecting data through observation, interviews and documentation with employees of the Land Office of Semarang City and the users of the service are community, notary, lurah, and staff of PPAT. The results of this study indicate that the implementation of SOP, the fulfillment of SPM and the participation of the community in the service has been well implemented. However, in the implementation there are still inhibiting factors that are uneven quality of apparatus resources, the implementation of limiting regulations in the simplification of SOP, and limitations in the operationalization of service infrastructure facilities. Some suggestions that can be made are improvements in administrative ordering, review of service standards to simplify SOP, increase socialization to the community related to procedures and programs of land services, rewarding to employees who perform well, and guidance of employees to improve discipline and awareness of employees as Community service.